Effects of prophylactic nalbuphine on emergence agitation and postoperative pain in pediatric patients undergoing ENT surgery with sevoflurane anesthesia - Han, Wendong; Cai, Jingjie; Zhang, Wangping; Wei, Rong; Jiang, Yan (Frontiers in Pediatrics, 2024)
Background: Emergence agitation (EA) is a common complication in the pediatric population. This study aimed to investigate the effect of the prophylactic nalbuphine on EA in pediatric patients receiving sevoflurane anesthesia. Methods: The children undergoing ear, nose, and throat (ENT) surgery were administered 0.2 mg/kg nalbuphine (the nalbuphine group) or the same volume of normal saline (the control group) 5 min before the end of the surgery. The extubating time, time to eye-opening and duration of the post-anesthesia care unit (PACU) were recorded. Heart rate and blood pressure were monitored before and 5 min after nalbuphine administration. Pain was assessed using Face Legs Activity Cry and Consolability (FLACC) scales, and the drug-related postoperative complications (e.g., EA, delayed awakening, nausea and vomiting, and respiratory depression) were recorded. Results: One-hundred and thirty pediatric patients were randomly divided into nalbuphine and control groups (n = 65). The nalbuphine group showed a significantly lower incidence of EA than the control group (20%vs 46.2%, P=0.002). No significant differences between the two groups were observed in heart rate and blood pressure 5 min after nalbuphine administration (P > 0.05). No significant differences were observed between the two groups regarding extubating time, time to eye-opening, and duration of PACU. The FLACC scales demonstrated lower values in the nalbuphine group than in the control group during the initial 4 hours after the surgery. However, the FLACC scales showed similar values between 5 and 12 hours after the surgery. Conclusions: In summary, the results of this study demonstrated that prophylactic nalbuphine could minimize the incidence of EA in pediatric patients receivfollowing ENT surgery without increasing the extubating time and PACU duration.